Is maternal pre-pregnancy Body Mass Index associated with type of Congenital Heart Disease in offspring? - Nofita Fachryandini; Taufiq Hidayat; Ernawati Ernawati; Mahrus A Rahman (Universitas Airlangga, 2023)
HIGHLIGHTS The most common CHD was atrial septal defect for acyanotic CHD and Tetralogy of Fallot for cyanotic CHD. There was no association between maternal pre-pregnancy BMI and type of CHD in offspring. ABSTRACT Objectives: This study aimed to determine the association between maternal pre-pregnancy BMI and type of congenital heart disease (CHD) in offspring. Materials and Methods: This retrospective cross-sectional study involved all mothers of children with CHD who visited Pediatric Outpatient Unit at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, from January to December 2019. The maternal data were obtained from the KIA's (Maternal and Child Health) book or through anamnesis by telephone, while the offspring’s data were collected from medical records. The data were analyzed using the Chi-Square test. Significance was determined at a 5% level (p <0.05). Results: We studied 117 mothers of children with CHD. The most frequent maternal pre-pregnancy body mass index (BMI) was normal (BMI 17-23 kg/m2) accounting for 56.4% of the study population. The most common CHD was atrial septal defect (33.3%) among acyanotic patients and Tetralogy of Fallot (8.5%) among cyanotic patients. The Chi-Square test showed p=0.958 for the association between maternal pre-pregnancy BMI and type of CHD in offspring. Conclusion: There was no association between maternal pre-pregnancy BMI and type of CHD in offspring.